Substitute -x-2 for y in 3x+3y=6
3x+3y=6
3x+3(-x-2)=6
-6=6 (Simplify both sides of the equation)
-6+6=6+6 ( add six to both sides)
0=12
Answer: No Solutions
Hope this helped
Set the bottom equal to 0
x - 8 = 0
x = 8
Answer:
1836.76666667
Step-by-step explanation:
pls join me
mnv-dyzw-eov
there will be nothing unsafe or inappropriate
I think it’s A?? Idk just my opinion I’m sorry if it’s wrong
Answer:
6. k=-18
9. a=-6
12. d= 24
Step-by-step explanation:
6. k/6 +8=5
first subtract 8
k/6= -3
now multiple by the reciprocal of k/6 which is 6
k=-18
9. 9+a/6=8
a/6= -1
a=-6
12. d/4- 9= -3
d/4=6
d= 24